Comparison of angiotensin converting enzyme -like activity in the Antarctic teleosts Trematomus bernacchii and Chionodraco hamatus. - QUASSINTI, Luana; MACCARI, Ennio; BRAMUCCI, Massimo; PELLEGRINO D; GAROFALO F (Polar Biology, 2009)
Biochemical parameters of the angiotensin converting enzyme-like activity (ACELA) in the gills of two Antarctic teleosts, Chionodraco hamatus and Trematomus bernacchii were characterized. Enzymatic activity was revealed following hydrolysis of a specific substrate of angiotensin-converting enzyme N-[3-(2-furyl)acryloyl]Lphenylalanyl-glycyl-glycine (FAPGG) and metabolites were separated by reverse phase HPLC analysis. The results showed similar Km values for the substrate FAPGG at 5°C for the two species with an increase of Km value for T. bernacchii at 25°C. The optimum pH value was 8.5 at 25°C and optimum chloride concentrations were about 300 mM. In T. bernacchii the optimum temperature for maximum enzyme activity was 50°C, while maximum activity in C. hamatus occurred at 35°C. Lisinopril was more effcient in inhibiting ACELA in C. hamatus with an I50 value of 16.83 ± 5.11 nM, compared to an I50 value of 30.66 ±5.19 nM in T. bernacchii. In conclusion, it appears that some biochemical parameters of ACELA in C. hamatus differ from those in T. bernacchii, probably due to different ways that the enzyme adapts to the constantly cold temperatures of the animal’s environment.